Determination of Iron, Copper and Zinc in the Wine by FAAS - Durguti, Valon Ylvi; Aliu, Suzana; Laha, Fisnik; Feka, Fidan (Ital Publication, 2020)
Objectives: The purpose of this paper has been to determine quantitatively the presence of some heavy metals (Fe, Cu and Zn) which are of particular importance for the wine quality and human health. A total of 41 samples have been analyzed during different stages of winemaking. Methods: The determination of heavy metals is done by analytical technique known as Flame Atomic Absorption Spectroscopy (FAAS). The limit set by the EU directive EC 606/2009 and International Office of Vine and Wine (OIV) has been taken as reference values. Results and Discussion: None of the analyzed samples has exceeded the limits set by the EU and OIV, excluding the type of white wine known as Rhine Riesling. In this sample the Cu concentration exceeds several times the permissible values. Findings: It has been observed that heavy metals immediately after the alcoholic fermentation process probably continue to remain even for a while in the upper part until wine sediment forms at the bottom of the tank. A higher concentration of heavy metals was observed in the samples taken from the bottom of the wine tank. Conclusion: The analyzed wines samples do not pose a risk in the future to human health.Â Doi: 10.28991/esj-2020-01240 Full Text: PDF